Effect of composting and vermicomposting on properties of particle size fractions - Hanc, Ales; Dreslova, Marketa (Bioresource technology, 2016)
The objectives of the study were to compare the effects of the composting and the vermicomposting processes on the distribution of particles into three size fractions, and to assess the agrochemical properties of the size fractions of the composts and the vermicomposts. Three different mixtures of biowaste were subjected to two thermophilic pre-composting, and then the mixtures were subsequently subjected to 5months composting and vermicomposting under laboratory conditions. Vermicomposting was able to achieve the finer and more homogeneous final product compared to composting. For compost, the highest portion of the finest fraction was achieved from products which originated from kitchen waste containing used paper, followed by digestate with straw, and finally sewage sludge with garden biowaste. In most cases, compost particles which were less than 5mm exhibited the better agricultural potential than coarser compost. However, agrochemical properties of the finest vermicompost exceeded classical compost.
Keywords: Oligochaeta; Paper; Biodegradation, Environmental; Compost; Particle Size; Particle size fractions; Agrochemical properties; Soil; Animals; Refuse Disposal; zvířata; velikost částic; papír; odpadní vody; Vermicompost; odpadky - odstraňování; půda; Sewage; biodegradace